Enhancing Intercultural Understanding Through Project- Based Learning: A Study in the Multicultural Class of SMAN 2 Muara Bungo - regina (Education Library, 2025)
Indonesia’s cultural diversity presents unique opportunities and challenges in education, particularly in fostering tolerance and intercultural understanding. This study examines the implementation of Project-Based Learning (PBL) in a multicultural classroom at SMAN 2 Muara Bungo, which reflects the diversity of theMuara Bungo community, including the Minangkabau, Javanese, Jambi, and Batak tribes. Using a qualitative approach, data were collected through observation and reflection on classroom experiences. Findings indicate the effectiveness of PBL in enhancing cross-cultural collaboration, with 87% of students activelyparticipating in heterogeneous group projects, such as cultural exhibitions. Teachers play a critical role in facilitating these interactions, although challenges such as limited resources and varying levels of student engagement remain. The study concludes that PBL is an effective tool for fostering cultural inclusion, enhancing collaboration, and equipping students with essential social skills. However, additional support for teachers and students is needed to maximize its potential. These results provide valuable insights for the development of multicultural education in Indonesia.